Evaluation of single-round infectious, chimeric dengue type 1 virus as an antigen for dengue functional antibody assays - Atsushi Yamanaka (2018)
Dengue fever and dengue hemorrhagic fever are endemic throughout tropical and subtropical countries. Four serotypes of dengue viruses (DENV-1 to DENV-4), each with several genotypes including various subclades, are co-distributed in most endemic areas. Infection-neutralizing and -enhancing antibodies are believed to play protective and pathogenic roles, respectively. Measurement of these functional antibodies against a variety of viral strains is thus important for evaluating coverage and safety of dengue vaccine candidates. Although transportation of live virus materials beyond national borders is increasingly limited, this difficulty may be overcome using biotechnology that enables generation of an antibody-assay antigen equivalent to authentic virus based on viral sequence information. A rapid system to produce flavivirus single-round infectious particles (SRIPs) was recently developed using a Japanese encephalitis virus (JEV) subgenomic replicon plasmid. This system allows production of chimeric SRIPs that have surface proteins of other flaviviruses. In the present study, SRIPs of DENV-1 (D1-SRIPs) were evaluated as an antigen for functional antibody assays. Inclusion of the whole mature capsid gene of JEV into the replicon plasmid provided higher D1-SRIP yields than did its exclusion in cases where a DENV-1 surface-protein-expressing plasmid was used for co-transfection of 293T cells with the replicon plasmid. In an assay to measure the balance between neutralizing and enhancing activities, dose (antibody dilution)-dependent activity curves in dengue-immune human sera or mouse monoclonal antibodies obtained using D1-SRIP antigen were equivalent to those obtained using DENV-1 antigen. Similar results were obtained using additional DENV-2 and DENV-3 systems. In a conventional Vero-cell neutralization test, a significant correlation was shown between antibody titers obtained using D1-SRIP and DENV-1 antigens. These results demonstrate the utility of D1-SRIPs as an alternative antigen to authentic DENV-1 in functional antibody assays. SRIP antigens may contribute to dengue vaccine candidate evaluation, understanding of dengue pathogenesis, and development of serodiagnostic systems. © 2014 Elsevier Ltd.